A mixed method evaluation of ecosystem services and services-to-ecosystems illuminates culturally important trees in a settled landscape - Jacqueline Hamilton; Murray M. Humphries; Elena M. Bennett (Ecosystems and People)
Biodiversity loss can lead to losses in ecological functions, ecosystem services, and cultural values. Yet, literature that empirically relates species’ ecological and cultural importance is scarce. We investigate tree species’ cultural importance in a settled landscape in Canada by combining biophysical plot sampling (n = 122) and semi-structured interviews (n = 31). We examined relationships between cultural importance, ecosystem services (benefits from trees), services-to-ecosystems (actions toward trees), and the abundance, mortality, and modification of trees. We found that tree abundance generally correlated with cultural emphasis. Maple was the most biophysically abundant and culturally important tree, associated with the greatest diversity of ecosystem services. However, some trees were mentioned disproportionately more frequently than their biophysical abundance, likely due to high mortality in the case of ash and cultural importance in the case of apples. Apple trees were culturally important and linked to the most diverse services-to-ecosystems. Our findings suggest that cultural importance relates to provisioning ecosystem services and services-to-ecosystems, which may, in turn, influence the abundance of these culturally important genera on the landscape. This connection between cultural importance and services-to-ecosystems could be a potential lever for wider biocultural conservation. This study contributes to ongoing discussions about cultural ecosystem services and highlights the importance of services-to-ecosystems in understanding human-nature relationships. The results have implications for protected area management, suggesting that reduced human-tree interactions could negatively impact biocultural values.